2011
DOI: 10.1007/s11243-011-9568-x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-donor N,N,O-tridentate ligands for palladium-catalyzed Suzuki reactions

Abstract: Efficient Suzuki-Miyaura cross-coupling reactions of arylboronic acids with aryl halides catalyzed by Pd/N,N,O-tridentate ligands, using methanol as solvent and K 3 PO 4 as base, afforded the corresponding cross-coupled biaryls in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The development of amine‐bridged bis(phenol) ligands that have a rigid framework with bulky N ‐aryl substituents on the ring nitrogen to restrict the rotation of the coordination group has rarely been explored . The presence of the nitrogen atom on the amine bridge seems to have a significant effect on the catalytic activity of the corresponding ligands . Previously, we also found that Pd/ 2 ‐ and Pd/ 3 ‐catalyzed arylhalides with arylboronic acid in methanol aqueous afford good to excellent yield of coupling products .…”
Section: Introductionmentioning
confidence: 99%
“…The development of amine‐bridged bis(phenol) ligands that have a rigid framework with bulky N ‐aryl substituents on the ring nitrogen to restrict the rotation of the coordination group has rarely been explored . The presence of the nitrogen atom on the amine bridge seems to have a significant effect on the catalytic activity of the corresponding ligands . Previously, we also found that Pd/ 2 ‐ and Pd/ 3 ‐catalyzed arylhalides with arylboronic acid in methanol aqueous afford good to excellent yield of coupling products .…”
Section: Introductionmentioning
confidence: 99%